Push or Pull: What Drives Emigration from Lithuania? - Kavalnis, Remigijus; Kasnauskiene, Gindrute (Organizations and Markets in Emerging Economies, 2022)
This article investigates the main economic and non-economic determinants of population emigration from Lithuania. Our study offers a new approach for modelling the push and pull factors considering the push–pull link. We construct the relative variables and deploy mixed models for the macro data of Lithuania and 24 European destinations over 2010–2019. Our findings reveal that such economic variables as relative economic welfare, unemployment and income inequality are the key push–pull factors. The study results indicate that changes in relative welfare have the highest power to change Lithuanian emigration with the main impact recorded the same year, while changes in relative income inequality and unemployment affect fewer emigrants, and it takes one year for the effect to materialise. The obtained higher importance of relative welfare compared to the average wage suggests that the goods and services provided by the state play a role in the personal cost–benefit calculation of prospective emigrants. This study addresses the research gap on the quantitative push–pull factor evaluation, the timing of their impact, connectivity of the push–pull factors and structural changes, providing a foundation for future research on the root causes of emigration.